Implementation of Democratic Character Values Through Integrative Learning for Madrasah Ibtidaiyah Students - Nurjali, Nurjali; Nisak, Sayida Khoiratun; Wulandari, Triyana; Mun'amah, Anatun Nisa (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
Education plays a crucial role in shaping democratic character in students, especially within madrasahs. Democratic character, which encompasses values such as freedom of expression, deliberation, equality, and social responsibility, is essential for developing individuals capable of active participation in community life. Madrasahs, as institutions integrating religious and general education, hold a strategic role in instilling these characteristics. An integrative learning approach, particularly in science subjects, proves effective in internalizing democratic values. Instruction involving discussion, collaboration, and problem-solving enables students to think critically, appreciate differing opinions, and collaborate in decision-making. Additionally, extracurricular activities serve as an important means for students to practice democratic values. However, implementing democratic character in madrasahs faces challenges, such as students' diverse backgrounds and limited facilities. Therefore, there is a need for continuous improvement in teacher training and facility enhancement to ensure more effective democratic education.